Keyakinan Makanan Dalam Perspektif Keperawatan Transkultural Pada Ibu Hamil - Novitasari, Yuli; Pratiwi, Arum (Jurnal Berita Ilmu Keperawatan, 2019)
Cultural have a role on nutritional status for pregnant mother because had some belief, like taboo to consume some food that precisely has good nutrition and needed by our body. One of culture in Indonesia that have something to believe about food is Javanese culture. This research aims to analyze food belief who related to Java culture about recommendation and taboo to some food. The method of this research is qualitative with an ethnographic approach. Respondent of five people selected by the consideration that the respondent has a lot of information for a later interview by using the recorder. The result shown that there have restriction and suggestion to certain food. Food that is prohibited is goat meat, salty food, pineapple, durian, spicy food, herb, watermelon, sweet food, and ice. That kind of food belief can danger for pregnant mother and embryo. Whereas the recommended foods are fish without scales and drink plenty of water. The finding of this food had an effort to improve health.